Chiari I malformation with neurogenic hypertension underwent suboccipital decompression: A case report - Steven Okta Chandra; I Putu Pramana Suarjaya; Ida Bagus Krisna Jaya Sutawan; Tjokorda Gde Agung Senapathi; Tjokorda Gde Bagus Mahadewa (Bali Journal of Anesthesiology)
Abstract Chiari malformations have a wide array of clinical symptoms related to compression of the craniocervical structure. An uncommon symptom is neurogenic hypertension, which remains controversial from its origin, its clinical clues that suggest the diagnosis, and the intervention best suited for its treatment. Several case reports suggest this disorder will resolve after suboccipital decompression reflecting compressive effect in its nature. An important structure thought to be involved in this disorder is the ventrolateral medulla. This structure has an important role in blood pressure control and has been studied extensively. We present a case of a 24-year-old woman diagnosed with Chiari I malformation experiencing hypertensive urgency intraoperatively when the surgeon decompressed the suboccipital structure. The finding was anticipated based on history taking which revealed the patient experienced the same condition with additional ventricular tachyarrhythmia prior incision of suboccipital skin. The case was canceled and the patient was stabilized in the intensive care unit before being referred to our hospital. Hypertension in the intraoperative period can cause morbidity and mortality. This condition requires immediate treatment once it is noticed. Multidisciplinary approach and diagnostic study preoperatively have an important role as a supplement for anesthesiologists in making a clinical decision intraoperatively for the sake of preventing morbidity and mortality.